Congestion control mechanism in VANET for safety messaging - Jian SUN; Hong-zhi LI; Ling-bo GUO; Sheng-lai CHEN (Tongxin xuebao)
In vehicular ad-hoc network (VANET), periodic safety messages (beacons) may consume the entire channel bandwidth in dense traffic, resulting in a saturated/congested channel. As a solution to the problem, a congestion control mechanism based on beacon frequency and communication radius adjusting was proposed. Firstly, a basic channel re-source allocation algorithm for periodic safety message (PSM) and event-driven safety message (EDSM) was proposed, which limits the beacon load level below a specific threshold and thus implicitly reserves enough bandwidth for EDSM. And then, according to the accuracy and probability of successful reception, the beacon frequency and communication radius dynamically was adjusted to control the number of vehicles in the channel, while maintaining the vehicular safety.